(untitled) (Fiep Bulletin - online, 2014)
The Hospitalization in Intensive Care Unit (ICU) is a critical moment in the life of the patients and their relatives, marked by the constant fight between life and death. Thus, this study had as objective to carry through a bibliographical revision about the related emotional aspects to the ICU as a synonymous of death in the perception of the patient, family and professionals of nursing. The used method was the bibliographical survey in virtual database (LILACS, MEDLINE), covering a period of ten years (1996- 2006). It was verified that the ICU is perceived as an unknown environment and little welcoming, associated to death and serious illness.